2021
DOI: 10.2147/ijn.s273883
|View full text |Cite
|
Sign up to set email alerts
|

The Adjuvant of α-Galactosylceramide Presented by Gold Nanoparticles Enhances Antitumor Immune Responses of MUC1 Antigen-Based Tumor Vaccines

Abstract: Background: Therapeutic tumor vaccines are one of the most promising strategies and have attracted great attention in cancer treatment. However, most of them have shown unsatisfactory immunogenicity, there are still few available vaccines for clinical use. Therefore, there is an urgent demand to develop novel strategies to improve the immune efficacy of antitumor vaccines. Purpose: This study aimed to develop novel adjuvants and carriers to enhance the immune effect of MUC1 glycopeptide antigen-based antitumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 53 publications
1
16
0
Order By: Relevance
“…NPs have been developed to deliver mRNA vaccines that encode the tumor antigen MUC1 to DCs in lymph nodes, thereby facilitating the activation and expansion of tumor-specific T cells [ 103 ]. The construction of MUC1 glycopeptide vaccines by presenting α-GalCer adjuvants and antigens on gold NPs has also been proposed; this technique can potentially enhance anti-tumor responses during cancer immunotherapy [ 104 ]. The MUC1 vaccine has been tested in combination with other drugs to increase its anti-tumor effects.…”
Section: Clinic Applicationmentioning
confidence: 99%
“…NPs have been developed to deliver mRNA vaccines that encode the tumor antigen MUC1 to DCs in lymph nodes, thereby facilitating the activation and expansion of tumor-specific T cells [ 103 ]. The construction of MUC1 glycopeptide vaccines by presenting α-GalCer adjuvants and antigens on gold NPs has also been proposed; this technique can potentially enhance anti-tumor responses during cancer immunotherapy [ 104 ]. The MUC1 vaccine has been tested in combination with other drugs to increase its anti-tumor effects.…”
Section: Clinic Applicationmentioning
confidence: 99%
“…Preclinical and clinical trials using α-GalCer have shown that this therapy is safe, exhibits durable activation, and increases the number of iNKT, NK, tumor-specific, CD4+, CD8+ T, and B cells ( 148 , 149 , 151 , 153 156 , 160 , 161 , 169 , 172 , 173 , 175 ). This activation is associated with increased serum levels of cytokines that stimulate the growth and function of T cells [IL-12 ( 150 , 175 ) and IL-2 receptors ( 175 )] and other factors that enhance natural killer cell activity (i.e., interferon gamma [IFN-γ] ( 150 , 155 , 156 , 158 , 161 , 163 , 172 ), CD16 ( 175 ), and tumor necrosis factor α [TNF-α]) and immune cell maturation (GMCSF) ( 164 ).…”
Section: α-Galactosylceramide (α-Galcer)mentioning
confidence: 99%
“…Furthermore, this treatment modality could potentially be applied in cancer metastasis treatment because a systemic anti-tumor immune reaction could be induced through the therapeutic agent DOX and PTT [109]. The capability of AuNPs to load and release nucleic acids exhibits great research potential in cancer immunotherapy, because PTT-induced hyperthermia or light-triggered drug release can be synergistically achieved with the delivery of nucleic acid immunoadjuvants, which protects these bio-therapeutics from inactivation or degradation [110]. For instance, it was reported that AuNPs can improve the effectiveness of CpG both in vitro and in vivo [111][112][113].…”
Section: Gold-based Nanomaterialsmentioning
confidence: 99%